2002
DOI: 10.1016/s0006-3495(02)75669-5
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin-CO Conformational Substate Dynamics: 2D Vibrational Echoes and MD Simulations

Abstract: Two-dimensional (2D) infrared vibrational echoes were performed on horse heart carbonmonoxymyoglobin (MbCO) in water over a range of temperatures. The A(1) and A(3) conformational substates of MbCO are found to have different dephasing rates with different temperature dependences. A frequency-frequency correlation function derived from molecular dynamics simulations on MbCO at 298 K is used to calculate the vibrational echo decay. The calculated decay shows substantial agreement with the experimentally measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(133 citation statements)
references
References 42 publications
8
125
0
Order By: Relevance
“…5,8,10 The simulated dynamics overestimate the dynamical line broadening while underestimating the static line broadening needed to describe the experimental linear spectrum and vibrational echo data. However, analysis of the vibrational δω(t) ) δω p (t) + δω H64 (t) + δω s (t)…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…5,8,10 The simulated dynamics overestimate the dynamical line broadening while underestimating the static line broadening needed to describe the experimental linear spectrum and vibrational echo data. However, analysis of the vibrational δω(t) ) δω p (t) + δω H64 (t) + δω s (t)…”
Section: Discussionmentioning
confidence: 93%
“…5,8,10,11,52 In this picture, the force exerted by the local electric field on the electric dipole of the CO induces a shift in the CO transition frequency. Therefore, the frequency fluctuates in time with the dynamics of the local electric field.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] It has been suggested that different electrostatic environments in the heme pocket arising from distinct structures are largely responsible for the observed bands. 9 The distal histidine His64 plays a prominent role in determining the CO stretching frequencies, but the tautomerization and orientation of this residue remain controversial.…”
mentioning
confidence: 99%